TINJAUAN ALTERNATIF PEMELIHARAAN SUNGAI TERDAMPAK PELUAPAN BANJIR BERDASARKAN PENILAIAN KONDISI MORFOLOGI SUNGAI AMANDIT - Farial Agoes, Herliyani; Hayati, Fitriani; Muhlis, Andriani (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2023)
In the watershed, if there are no adequate maintenance alternatives for the morphology of the river, both the river infrastructure and the river itself can result in physical and functional degradation so that the effectiveness of the river as a natural airflow will be disrupted, flow control will not be optimal as experienced by the Amandit Kandangan River. The method to the Guidelines for the Implementation of River Infrastructure Operations Activities and River Maintenance (SE DJSDA No. 05/SE/D/2016). At STA 3+000 s.d. 6+500 is a segment with a decreased performance value of around 76.48, compared to the initial section of the range of 80.29 and the final section of the range of 80.28. This shows a decrease in the performance of the river in the middle of the sections due to airflow obstructions such as goods/materials in the troughs or bends in the river accompanied by narrowing in the middle section of the sections and often causes overflow due to the solubility of the airflow. Recommendations given are based on the results of an assessment of the overall morphological condition of the river, with the acquisition of an index in the sufficient category and the type of preventive maintenance.